Evaluation the virus resistance stability of T1 transgenic tobacco lines carrying RNAi TMV and RNAi TCYS construct - Thuy, Le Thi; Van, Pham Thi; Doai, Nguyen Van; Nhan, Lam Dai; Son, Le Van (Academia Journal of Biology, 2016)
Creating antiviral transgenic plants using RNAi technique is a modern and effective method to significantly reduce yield losses by plant viral diseases. In the previous publication, we had created some K326 and C9-1 transgenic tobacco lines containing RNAi TMV and RNAi TCYS construct with completely resisting to virus. In this study, the stability of transgene structure and virus resistance ability in the transgenic tobacco lines continue to be evaluated in the T1 generation. The results showed that the ten transgenic lines carrying RNAi TMV construct and 6 lines carrying RNAi TCYS are transgene segregation ratio of 3:1. PCR analyses using specific primers compined Southern blot analyses, compined Northern blot analyses proved the heredity and activity of transgene in both of K326 and C9-1 transgenic tobacco lines. The result of resistant test by virus infection of 10 lines containing RNAi TMV construct revealed that all of them completely resist to TMV with resistant ratio ranged from 5% to 20%. In RNAi TCYS construct, there were 3 lines with 3 individual plants completely resisting to four virus (TMV, CMV, TYLCV and TSWV) in population of 120 individual plants of 6 lines. The results of this study showed that the virus resistance transfered to T1 generation, opening opportunity to develope antiviral transgenic tobacco varieties in our country.